Tinjauan Hukum Ekonomi Syari’ah terhadap Praktik E-Commerce dengan Sistem Pembayaran Kredit Shopee PayLater - Suwarno (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
The practice of payment through the credit system in the e-commerce industry, especially through platforms like Shopee PayLater, has become a phenomenon increasingly dominating modern business transactions. This article aims to provide an in-depth review regarding the "Sharia Economic Law on the Practice of E-commerce with Credit Payment Systems." Using a literature review approach, this article seeks to better understand whether e-commerce practices with credit payment systems can be considered in line with Islamic Sharia values. As a result, it is expected that this article will offer profound and relevant insights into the marriage between modern digital business and the principles of Sharia economic law.